Connections between the Atlantic and the Amazonian forest avifaunas represent distinct historical events - Batalha-Filho, Henrique; Fjeldså, Jon; Fabre, Pierre-Henri; Miyaki, Cristina Yumi (Journal of ornithology, 2013)
There is much evidence to support past contact between the Atlantic and the Amazon forests through the South American dry vegetation diagonal, but the spatiotemporal dynamics of this contact still need to be investigated to allow a better understanding of its biogeographic implications for birds. Here, we combined phylogenetic data with distributional data using a supermatrix approach in order to depict the historical connection dynamics between these biomes for New World suboscines. We examined the variation in divergence time and then compared the spatial distributions of taxon pairs representing old and recent divergences. Our results pointed to two distinct spatiotemporal pathways connecting the Atlantic and the Amazonian forests in the past: (1) old connections (middle to late Miocene) through the current southern Cerrado and Mato Grosso and the transition towards the Chaco and palm savannas of Bolivia and Paraguay; (2) young connections (Pliocene to Pleistocene) that possibly occurred through the Cerrado and Caatinga in northeastern Brazil. We suggest that the main events that played important roles in these connections were geotectonic events during the late Tertiary associated with the uplift of the Andes (old connections) and Quaternary climate changes that promoted the expansion of gallery forest through the Cerrado and Caatinga in northeastern Brazil (young connections). Our results provide the first general temporal and spatial model of how the Atlantic and Amazonian forests were connected in the past, which was derived using bird data.